Social capital and its relationship with malnutrition and anemia in children from rural coastal Ecuador - José Caicedo-Gallardo; María Rivadeneira; Ana Torres; Betzabé Tello; Fabricio Astudillo; Gladys Buitrón; Ana Moncayo (James Cook University, 2021)
Introduction: Social capital is considered an important determinant of health and overall wellbeing; however, to the best of the authors' knowledge, literature relating social capital to malnutrition in developing countries is still relatively small. This article examines the relationships between social capital and chronic malnutrition and anemia in a population of rural coastal children in Ecuador. Methods: A cross-sectional study in two groups of 246 and 282 children under 5 years and their families was performed. Anemia and chronic malnutrition were analyzed as outcome variables. Variables about social capital were identified on the basis of the Social Capital Assessment Tool of the World Bank. Bivariate and multivariate logistic regression analyses were conducted. Results: The prevalences of anemia and chronic malnutrition in the children were 15.0% and 12.8%, respectively. At the multivariate analysis, the variable 'mother has borrowed money' had an inverse association with chronic malnutrition (prevalence ratio (PR) 0.43, 95% confidence interval (CI) 0.20-0.90). Receiving and providing help after the earthquake of 2016 was significantly associated with a lower prevalence of chronic malnutrition (PR 0.52, 95%CI 0.28-0.97), but not with anemia. However, a mother being part of a community organization was associated with a 1.90 times higher prevalence of anemia (95%CI 1.04-3.48) in children than mothers who were not part of a community organization. Conclusion: The relationship between maternal social capital and the nutritional status of their children in rural communities seems to be positively related. However, a mother's participation in community organizations increases the prevalence of anemia in the children. These mixed results highlight the need for further studies focused on the different types of social capital and how they impact on health in deprived areas.